2009
DOI: 10.1002/j.2055-2335.2009.tb00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness and Clinical Impact of Hospital‐Initiated Medication Reviews

Abstract: Background: Medication-related problems often occur in the immediate post-discharge period. To reduce medication misadventure the Commonwealth Government funds home medicines reviews (HMRs). HMRs are initiated when general practitioners refer consenting patients to their community pharmacists, who then engage accredited pharmacists to review patients' medicines in their homes. Aim: To determine if hospital-initiated medication reviews (HIMRs) can be implemented in a more timely manner than HMRs; and to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…1). Data were extracted from nine controlled studies (Table 1), 20-28 34 observational or uncontrolled studies with a focus on MRPs (Table 2), [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and other clinical, humanistic and economic outcomes (Table 3), 10,44-61 11 qualitative (including interviews and focus groups) and nine survey research studies (Table 4). 11,13,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Methodological quality of studies…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Data were extracted from nine controlled studies (Table 1), 20-28 34 observational or uncontrolled studies with a focus on MRPs (Table 2), [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and other clinical, humanistic and economic outcomes (Table 3), 10,44-61 11 qualitative (including interviews and focus groups) and nine survey research studies (Table 4). 11,13,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Methodological quality of studies…”
Section: Resultsmentioning
confidence: 99%
“…32 Three studies were excluded from this calculation due to insufficient information. [37][38][39] One study reported a mean of 7.2 'issues' per CMR for people with a mental illness, although some 'issues' were prescriber or patient-related rather than medication-related. 30 Only one study included a comparator group, finding a greater number of MRPs identified by a CMR pharmacist integrated in a GP clinic in comparison to an external CMR pharmacist (5.4 vs 3.6 MRPs per patient).…”
Section: Clinical and Humanistic Outcomesmentioning
confidence: 98%
See 3 more Smart Citations